Atlas of the OMERACT Heel Enthesitis MRI Scoring System (HEMRIS). Issue 1 (11th February 2020) - Mathew, Ashish J; Krabbe, Simon; Eshed, Iris; Lambert, Robert GW; Laredo, Jean-Denis; Maksymowych, Walter P; Gandjbakhch, Frederique; Emad, Yasser; Stoenoiu, Maria Simona; Foltz, Violaine; Bird, Paul; Carron, Philippe; et al.
Abstract : Objective: Assessment of enthesitis, a key feature in spondyloarthritis (SpA) and psoriatic arthritis (PsA), using objective and sensitive methods is pivotal in clinical trials. MRI allows detection of both soft tissue and intra-osseous changes of enthesitis. This article presents an atlas for the Outcome Measures in Rheumatology (OMERACT) Heel Enthesitis Magnetic Resonance ImagingMRI Scoring System (HEMRIS). Methods: Following a preliminary selection of potential examples of each grade, as per HEMRIS definitions, the images along with detailed definitions and reader rules were discussed at web-based, interactive meetings between the members of the OMERACT MRI in Arthritis Working Group. Results: Reference images of each grade of the MRI features to be assessed using HEMRIS, along with reader rules and recommended MRI sequences are depicted. Conclusion: The presented reference images can be used to guide scoring Achilles tendon and plantar fascia (plantar aponeurosis) enthesitis according to the OMERACT HEMRIS in clinical trials and cohorts in which MRI enthesitis is used as an outcome.